Antibody-functionalized gold nanoparticles as tumor-targeting radiosensitizers for proton therapy. (24th January 2019) - Li, Sha; Bouchy, Sandra; Penninckx, Sebastien; Marega, Riccardo; Fichera, Ornella; Gallez, Bernard; Feron, Olivier; Martinive, Philippe; Heuskin, Anne-Catherine; Michiels, Carine; Lucas, Stéphane
Aim: This study aimed at developing antibody-functionalized gold nanoparticles (AuNPs) to selectively target cancer cells and probing their potential radiosensitizing effects under proton irradiation.Materials & methods: AuNPs were conjugated with cetuximab (Ctxb–AuNPs). Ctxb–AuNP uptake was evaluated by transmission electron microscopy and atomic absorption spectroscopy. Radioenhancing effect was assessed using conventional clonogenic assay.Results & conclusion: Ctxb–AuNPs specifically bound to and accumulated in EGFR-overexpressing A431 cells, compared with EGFR-negative MDA-MB-453 cells. Ctxb–AuNPs enhanced the effect of proton irradiation in A431 cells but not in MDA-MB-453 cells. These data indicate, for the first time, that combining enhanced uptake by specific targeting and radioenhancing effect, using conjugated AuNPs, is a promising strategy to increase cell killing by protontherapy.